2017
DOI: 10.1080/07352166.2017.1373023
|View full text |Cite
|
Sign up to set email alerts
|

“Barcelona in common”: A new urban regime for the 21st-century tourist city?

Abstract: A coalition of leftist political groups, civic movements, and grassroots organizations led by social activist Ada Colau has won the Barcelona municipal elections of 2015, and is now governing the Catalan capital. The key to this success may well have been its critical positioning in relation to its tourism. Until recently considered a best practice in urban regeneration and a successful global destination, Barcelona has lived in the last two years a radical change in the public perception on tourism: from 'man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 58 publications
0
62
0
7
Order By: Relevance
“…The debate surrounding overtourism has helped to draw attention to the negative consequences of unconstrained tourism growth. In doing so, it has pointed towards limitations of market-oriented voluntary approaches to effectively deal with this issue [1]. Instead, possibilities for more regulatory, government-led approaches to manage tourism that seemed to have gone out of fashion since the start of the century were up for discussion again [16,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate surrounding overtourism has helped to draw attention to the negative consequences of unconstrained tourism growth. In doing so, it has pointed towards limitations of market-oriented voluntary approaches to effectively deal with this issue [1]. Instead, possibilities for more regulatory, government-led approaches to manage tourism that seemed to have gone out of fashion since the start of the century were up for discussion again [16,56].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, until recently, tourism was seen as one of the more sustainable economic growth strategies for cities. Particularly in the aftermath of the economic crisis of 2008, it was viewed as an important driver for economic recovery or growth and it was given plenty of scope to develop, thus reinforcing the relative importance of the industry in city destinations [1].…”
Section: The Rise Of Overtourismmentioning
confidence: 99%
“…It showed that "tourists" may be "already there", experiencing places similarly to conventional tourists, but preceded or followed by everyday (local) activities. As such, they may visit these destinations throughout the year, at their own pace and convenience, and without the disruptive force of mass influx from elsewhere (Russo & Scarnato, 2018). They add less negative external effects such as pollution and congestion, do not reproduce social and spatial transport inequalities, and do not have the dispossessive impact of (over)tourism on housing, retail, and the local fabric.…”
Section: Discussionmentioning
confidence: 99%
“…In a very short time, the term overtourism has become a descriptor of the negative impact of tourism and refers to the problem of excess tourists in many cities. The discussion around overtourism has drawn attention to the negative consequences of unlimited tourism growth and also pointed out directions of restrictions and voluntary compromises aimed at effectively preventing growing problems [18].…”
Section: Overtourism and How To Measure Itmentioning
confidence: 99%